2011
DOI: 10.1002/bjs.7497
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cellular effects of hypothermia, acidosis and coagulopathy in major injury

Abstract: The triad of hypothermia, acidosis and coagulopathy after severe trauma appears to be fairly rare but does carry a poor prognosis. Future research should define modes of early detection and targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 130 publications
(201 reference statements)
0
41
0
8
Order By: Relevance
“…Vasoconstriction is due not only to the injury itself but also to what is known as the lethal triad-an intricately connected combination of hypothermia, acidosis, and coagulopathy commonly associated with trauma ( Figure 2). 16 Hypothermia-associated coagulopathy occurs when core temperature decreases to less than 33°C (91.4°F). Reprinted from Thorsen et al, 16 with permission.…”
Section: Pathophysiology Of Trauma and Associated Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…Vasoconstriction is due not only to the injury itself but also to what is known as the lethal triad-an intricately connected combination of hypothermia, acidosis, and coagulopathy commonly associated with trauma ( Figure 2). 16 Hypothermia-associated coagulopathy occurs when core temperature decreases to less than 33°C (91.4°F). Reprinted from Thorsen et al, 16 with permission.…”
Section: Pathophysiology Of Trauma and Associated Hemorrhagementioning
confidence: 99%
“…16 Hypothermia-associated coagulopathy occurs when core temperature decreases to less than 33°C (91.4°F). Reprinted from Thorsen et al, 16 with permission. (defined as prothrombin time > 14 seconds and partial thromboplastin time > 34 seconds) was an independent predictor of mortality in patients with major trauma, increasing their risk of death by 35%.…”
Section: Pathophysiology Of Trauma and Associated Hemorrhagementioning
confidence: 99%
“…In vivo animal models [5] and clinical studies [6] demonstrated an association between coagulopathy and hypothermia. Laboratory studies show that decreased temperature inhibits platelet function [7,8] and the activity of enzymes involved in the co-…”
Section: Introductionmentioning
confidence: 99%
“…It can be caused by the loss of coagulation factors due to haemorrhage, hypothermia, acidosis, trauma and dilution from the intravenous fluids (IVF) administration [3][4][5]. The circulatory system can be viewed as an electrical circuit (P= F x R) in which P represents pressure difference between the two ends of the vessel, F is blood flow and R is called the vascular resistance [6].…”
Section: Introductionmentioning
confidence: 99%